Exploring the retention properties of CaF2 nanoparticles as possible additives for dental care application with tapping-mode atomic force microscope in liquid - Wasem, Matthias; Köser, Joachim; Hess, Sylvia; Gnecco, Enrico; Meyer, Ernst (Beilstein Journal of Nanotechnology, 2014)
Amplitude-modulation atomic force microscopy (AM-AFM) is used to determine the retention properties of CaF2 nanoparticles adsorbed on mica and on tooth enamel in liquid. From the phase-lag of the forced cantilever oscillation the local energy dissipation at the detachment point of the nanoparticle was determined. This enabled us to compare different as-synthesized CaF2 nanoparticles that vary in shape, size and surface structure. CaF2 nanoparticles are candidates for additives in dental care products as they could serve as fluorine-releasing containers preventing caries during a cariogenic acid attack on the teeth. We show that the adherence of the nanoparticles is increased on the enamel substrate compared to mica, independently of the substrate roughness, morphology and size of the particles.
Keywords: AM-AFM in liquid; nanodentistry; nanoparticles